Museums and sites of persuasion politics, memory and human rights - Apsel, Joyce; Sodaro, Amy (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2020)
Museums and Sites of Persuasion examines the concept of museums and memory sites as locations that attempt to promote human rights, democracy and peace. Demonstrating that such sites have the potential to act as powerful spaces of persuasion or contestation, the book also shows that there are perils in the selective memory and history that they present. Examining a range of museums, memorials and exhibits in places as varied as Burundi, Denmark, Georgia, Kosovo, Mexico, Peru, Vietnam, and the US, this volume demonstrates how they represent and try to come to terms with difficult histories. As sites of persuasion, the contributors to this book argue, their public goal is to use memory and education about the past to provide moral lessons to visitors that will encourage a more democratic and peaceful future. However, the case studies also demonstrate how political, economic, and social realities often undermine this lofty goal, raising questions about how these sites of persuasion actually function on a daily basis. Straddling several interdisciplinary fields of research and study, Museums and Sites of Persuasion will be essential reading for those working in the fields of museum studies, memory studies, and genocide studies. It will also be essential reading for museum practitioners and anyone engaged in the study of history, sociology, political science, anthropology and art history.
Part I: Museums, politics and persuasion: Joyce Apsel and Amy Sodaro, Introduction: memory, politics and human rights -- 1. Amy Sodaro, Selective memory: memorial museums, human rights, and the politics of victimhood -- Part II: Writing national histories: 2. Malkhaz Toria, Between traditional and modern museology: exhibiting national history in the Museum of Georgia -- 3. Astrid Nonbo Andersen, Curating enslavement and the colonial history of Denmark: The 2017 Centennial -- 4. Alissa Boguslaw, Kosovo's NEWBORN monument: persuasion, contestation, and the narrative constructions of past and future -- Part III: Displaying difficult pasts -- 5. Joyce Apsel, "Inspiration lives here": struggle, martyrdom and redemption in Atlanta's Center for civil and human rights -- 6. Roy Tamashiro, The son my memorial and museum: a continuous memorial service to remember and bear witness to the 1968 My Lai Massacre -- 7. Joseph P. Feldman, Memory as persuasion: historical discourse and moral messages at Peru's place of memory, tolerance, and social inclusion -- Part IV: Resistance through memory -- 8. Benjamin Nienass and Alexandra Delano Alonso, Mexico City's memorial to the victims of violence and the facade of participation -- 9. Sixte Vigny Nimuraba and Douglas Ivrin-Erickson, Narratives of ethnic and political conflict in Burundian sites of persuasion -- Joyce Apsel and Amy Sodaro, Conclusion.
Includes bibliographical references (pages [198]-211) and index.
Keywords: Museums -- Political aspects; Collective memory; Human rights -- Museums -- Social aspects; Memorials -- Social aspects; Persuasion (Psychology).